THE DECISION OF THE ROMANIAN CONSTITUTIONAL COURT (RCC) NO. 412 OF 24 SEPTEMBER 2025 – (IN)COMPATIBILITY WITH THE PRINCIPLE OF INDEPENDENCE OF REGULATORY AUTHORITIES PROVIDED FOR BY EUROPEAN LEGISLATION - Zorzoană, Ionela Alina (International Journal of Legal and Social Order, 2025)
The study examines the considerations of Decision no. 412/2025 of the Constitutional Court, relating them to the requirements of institutional independence of regulatory authorities, enshrined in the norms and case law of the European Union. The originality of the study lies in its comparative perspective on the Court's reasoning and the Romanian state's obligations under EU law, particularly regarding the protection of the functional, organizational, and financial autonomy of these entities. The analysis highlights the fact that the pronounced solution allows for excessive political interference in the organization and exercise of regulatory powers, which may affect their impartiality and neutrality. It will be emphasized that the lack of adequate guarantees of independence contravenes the standards set out in the sectoral directives and the case law of the Court of Justice of the European Union, thereby creating grounds for possible non-conformity of domestic law. The study draws attention to the risk of a conflict of norms, likely to lead to infringement procedures against Romania. The conclusion will support the need for a constitutional interpretation that integrates European standards, ensuring the effectiveness of the principle of autonomy of regulatory authorities and compliance with the commitments assumed by the Romanian state within the Union.